2007
DOI: 10.2134/agronj2006.0288
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Effects on Partitioning, Yield, and Earliness of Contrasting Cotton Cultivars

Abstract: Potassium nutrition requirements may differ in cotton (Gossypium hirsutum L.) cultivars that contrast in maturity and growth habit. Our objectives were to determine the effects of K fertility on carbohydrate and biomass partitioning, earliness, and lint yields of two contrasting cultivars. Fertilizer rates of 56 and 112 kg K ha 21 yr 21 , representing 13 and 23 recommended K rates, were applied to long-term K fertility plots on a no-tilled Loring silt loam (thermic Oxyaquic Fragiudalf) in Jackson, TN. Plant sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
4
16
1
2
Order By: Relevance
“…Significant growth responses to additional K were thus observed only rarely, but more often in vegetative than reproductive organs. Results are consistent with those of Clement‐Bailey and Gwathmey (2007)…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Significant growth responses to additional K were thus observed only rarely, but more often in vegetative than reproductive organs. Results are consistent with those of Clement‐Bailey and Gwathmey (2007)…”
Section: Resultssupporting
confidence: 90%
“…Yields of FM 960 and DP 555 were equivalent in 2006 and 2007, although yields of the two cultivars tended ( P = 0.068) to respond differently to K in 2007 (Table 1). There were no significant cultivar × K interactions for yield in this study, unlike the earlier study of Clement‐Bailey and Gwathmey (2007) These researchers reported that PM 1218 yielded about 9% less than DP 555 at the 56‐kg K rate, but that the two cultivars produced equivalent yields with 112 kg K ha −1 Like the current study, however, Clement‐Bailey and Gwathmey (2007) reported a delay in harvest maturity of both cultivars with the higher K fertilization rate.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…This may cause a greater proportion of photosynthates to be translocated to above-ground organs of Bollgard varieties rather than the roots, thus resulting in lower root densities than in non-Bollgard varieties. Our observation support the reports by some authors (Clement-Bailey and Gwathmey, 2007;Hulugalle et al, 2014) that root density of Bollgard 1 cotton in some depths was less than that in the corresponding non-Bollgard cotton variety. Clement-Bailey and Gwathmey (2007) have suggested that the lower root densities in Bollgard cotton may reduce potassium uptake.…”
Section: Cottonsupporting
confidence: 93%
“…The indeterminate MG IV soybean cultivars tend to have a slightly shorter growing season and may be more susceptible to yield loss from nutrient deficiency than the determinate MG V cultivars. Although we could find no conclusive information for soybean, short‐season cotton ( Gossypium hirsutum L.) cultivars are reported to be more sensitive to K deficiency than long‐season cultivars (Tupper et al, 1996; Clement‐Bailey and Gwathmey, 2007). The growth differences between determinate and indeterminate soybean cultivars suggest that their response to K deficiency could be different.…”
mentioning
confidence: 73%